2020
DOI: 10.3390/s20175009
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous Energy Harvester Based on Textile-Based Enzymatic Biofuel Cell for On-Demand Usage

Abstract: This paper presents an autonomous energy harvester based on a textile-based enzymatic biofuel cell, enabling an efficient power management and on-demand usage. The proposed biofuel cell works by an enzymatic reaction with glucose in sweat absorbed by the specially designed textile for sustainable and efficient energy harvesting. The output power of the textile-based biofuel cell has been optimized by changing electrode size and stacking electrodes and corresponding fluidic channels suitable for following power… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…With the development of semiconductor technology, large-scale integrated circuits with high integration and powerful functions continue to appear, which makes electronic equipment continue to shrink and reduce its weight. How to reduce the switching power supply is an important direction of switching power supply research [9][10][11], which requires the study of DC-DC converter topology, new materials, highperformance electronic components, etc. [12].…”
Section: Introductionmentioning
confidence: 99%
“…With the development of semiconductor technology, large-scale integrated circuits with high integration and powerful functions continue to appear, which makes electronic equipment continue to shrink and reduce its weight. How to reduce the switching power supply is an important direction of switching power supply research [9][10][11], which requires the study of DC-DC converter topology, new materials, highperformance electronic components, etc. [12].…”
Section: Introductionmentioning
confidence: 99%
“…Making the EBFC system is essential for the application involved. For example, to detect blood glucose, the EBFC system developed should be easy to use and dispose of [77]. Most EBFC systems exhibit decreased power and limited lifetime because solvent evaporation in the hydrostatic electrolyte and biofuel depletion require paper exchange replacement and electrolyte refilling [77].…”
Section: System In Ebfcmentioning
confidence: 99%
“…For example, to detect blood glucose, the EBFC system developed should be easy to use and dispose of [77]. Most EBFC systems exhibit decreased power and limited lifetime because solvent evaporation in the hydrostatic electrolyte and biofuel depletion require paper exchange replacement and electrolyte refilling [77]. To reduce external components such as pumps, Duong et al [17] have produced self-pumping EBFCs, as shown in Figure 7.…”
Section: System In Ebfcmentioning
confidence: 99%
See 1 more Smart Citation